Place of Blockchain in the System of Copyright Objects - Teremetskyi, Vladyslav; Maliar, Stanislav (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
Existing legal regimes of blockchain protection have been studied in the article. The emphasis has been put on the complexity of the blockchain legal protection, which consists in the fact that this object covers two subgroups: information and objects of intellectual property rights. This object is the system for recording, storing and processing information and technology for action in the digital environment. It has been proved that a blockchain is a value that is related to the objects of exclusive rights and can have tradability. The value of the blockchain is that each record in its system is stored, which creates conditions for the impossibility of abuse of subjective rights that are recorded and used by this object, because the actions implemented in the system can be viewed and therefore possible replacement can be found. It has been found out that the blockchain has the following legal characteristics: 1) it is a complex object (combines its own structural elements and the data contained there); 2) it has an objective digital form; 3) it is an intangible asset capable for tradability; 4) it can be attributed to documents that record information; 5) it is a database that operates in conjunction with a computer program; 6) it has different legal regimes of protection; 7) it satisfies the needs of consumers in the storage, processing of information, the implementation of certain legal actions in the digital environment. It has been established that depending on the information included in the blockchain, it is possible to distinguish the areas of its use, as well as its types. It has been emphasized that the blockchain can be considered as an object of copyright in the form of a composed title that combines a database and a computer program. In this case, blockchain within the information law can be considered as an information product in the form of a document containing information. Blockchain can also receive patent and legal protection in the form of an invention (method and product). At the same time, it has been emphasized that it is a narrow approach to study the blockchain exclusively through the prism of patent and legal protection. It has been substantiated that the development of legal protection in the field of intellectual property proves the need for applying different regimes of legal protection.